The Reader's Digest children's atlas of the world - Sale, Colin (Reader's Digest Children's Books, 1998)
Includes more than fifty maps; a fact file on each country and territory; illustrations of places, people, landscapes, and wildlife; an introduction to map making and map reading; projects; activities; and quizzes.